Corporate Entrepreneurship Driven by Big Data Analytics Capability: A Perspective Based on the Generation and Utilization of Slack Resources - Yadan Zheng; Lihua Dai (SAGE Open)
With the escalating significance of big data analytics, firms are contemplating strategies to incorporate the transformative effects of these digital technologies into their competitive frameworks. However, the persistent ‘IT productive paradox’ phenomenon highlights that the issue of how firms implement and manage big data analytics remains unresolved. Drawing on resource orchestration theory and organizational inertia theory, this paper aims to explore the relationship between big data analytics capability and corporate entrepreneurship. The research data are collected from 206 Chinese firms engaged in big data analytics activities. The hierarchical regression and bootstrap analysis results indicate a positive relationship between big data analytics capability and corporate entrepreneurship, with organizational slack plays a partial mediating role in this relationship. Additionally, organizational flexibility can strengthen the positive relationship between big data analytics capability and organizational slack, while performance aspiration matching can weaken the positive relationship between organizational slack and corporate entrepreneurship. The findings offer new insights into how and when big data analytics capability can create value. Overall, this study provides a crucial theoretical foundation for firms to leverage big data analytics technology in executing digital transformation and achieving business upgrading.